Community Empowerment Through Red Onion Cultivation with Polybags on 1 Ilir Urban Village, Palembang City - Hawayanti, Erni; Siti Aminah, Iin; Syahputra, Nico; Moulyohadi, Yopie; Tri Astuti, Dessy (Altifani Journal: International Journal of Community Engagement, 2021)
1 Ilir Urban Village is a village located on the Musi River edge. These Urban Village is quite broad, however underdeveloped area compared to other places in the city of Palembang. Many people live below the poverty line, lack green open space, and have inadequate educational facilities. Most of the population earns a living as laborers, while the women are ordinary housewives. To increase the income of homemakers in helping to improve the family's economy, we conduct training to increase community knowledge in red onion cultivation in polybags by utilizing a narrow yard of the house. The purpose of the activity is to provide motivation, knowledge, and skills to residents, especially housewives, by using the house's yard for onion cultivation to increase productivity and welfare. The methods used to achieve the objectives are surveys, counseling, and training the community on the use of yard land for onion cultivation in polybags and direct practice of red onion cultivation. Based on the process and results of the service that has been carried out, the training participants are very enthusiastic and understand and can carry out onion cultivation in polybags.